2002
DOI: 10.1038/ng823
|View full text |Cite
|
Sign up to set email alerts
|

Germline mutations in the ribonuclease L gene in families showing linkage with HPC1

Abstract: Although prostate cancer is the most common non-cutaneous malignancy diagnosed in men in the United States, little is known about inherited factors that influence its genetic predisposition. Here we report that germline mutations in the gene encoding 2'-5'-oligoadenylate(2-5A)-dependent RNase L (RNASEL) segregate in prostate cancer families that show linkage to the HPC1 (hereditary prostate cancer 1) region at 1q24-25 (ref. 9). We identified RNASEL by a positional cloning/candidate gene method, and show that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
308
3
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 467 publications
(321 citation statements)
references
References 21 publications
7
308
3
3
Order By: Relevance
“…RNase L was initially proposed to be a candidate tumor suppressor by us and Peter Lengyel based on its involvement in the antiproliferative activity of IFN and on the location of RNASEL at chromosome 1q25, a region deleted or rearranged in some breast cancers [89][90][91]. However, specific evidence of a role for RNase L in the suppression of cancer had to wait almost 10 years, until the long sought, hereditary prostate cancer 1 (HPC1) was mapped to the RNase L gene by the group of Jeff Trent [92]. Several germline mutations or variants in HPC1/RNASEL have been observed in hereditary prostate cancer [92][93][94][95] (reviewed in ref.…”
Section: The Role Of Rnase L In Hereditary Prostate Cancer and Discovmentioning
confidence: 99%
See 2 more Smart Citations
“…RNase L was initially proposed to be a candidate tumor suppressor by us and Peter Lengyel based on its involvement in the antiproliferative activity of IFN and on the location of RNASEL at chromosome 1q25, a region deleted or rearranged in some breast cancers [89][90][91]. However, specific evidence of a role for RNase L in the suppression of cancer had to wait almost 10 years, until the long sought, hereditary prostate cancer 1 (HPC1) was mapped to the RNase L gene by the group of Jeff Trent [92]. Several germline mutations or variants in HPC1/RNASEL have been observed in hereditary prostate cancer [92][93][94][95] (reviewed in ref.…”
Section: The Role Of Rnase L In Hereditary Prostate Cancer and Discovmentioning
confidence: 99%
“…However, specific evidence of a role for RNase L in the suppression of cancer had to wait almost 10 years, until the long sought, hereditary prostate cancer 1 (HPC1) was mapped to the RNase L gene by the group of Jeff Trent [92]. Several germline mutations or variants in HPC1/RNASEL have been observed in hereditary prostate cancer [92][93][94][95] (reviewed in ref. [96]), including a common (35% allelic frequency) missense variant of RNase L, in which a G to A transition at nucleotide position 1385 (G1385A) results in a glutamine instead of arginine at amino acid position 462 (R462Q).…”
Section: The Role Of Rnase L In Hereditary Prostate Cancer and Discovmentioning
confidence: 99%
See 1 more Smart Citation
“…9 The role of the ''2 0 -5 0 A-system'' in the control of cellular growth suggests that defects in this pathway could result in reduced immunity to virus infections and cancer. 10 The first evidence implicating RNASEL as a tumor suppressor gene was the recent identification of this gene as the candidate for the hereditary prostate cancer 1 (HPC1) gene by Carpten et al 11 They identified the RNASEL nonsense mutation Glu265X that segregated with the disease in one prostate cancer family. This same mutation has been identified in further prostate cancer families, although not always with evidence of segregation with the disease.…”
mentioning
confidence: 99%
“…Many susceptibility genes for prostate cancer exist, and HPCX and RNASEL have been reported. 7,8 A genetic linkage study showed an association between familial risk of brain and prostate cancers and the 1p36 chromosome locus. 9 In previous studies on the effects of lipoproteins on prostate cancer proliferation and migration, we found that remnant lipoprotein or high-density lipoprotein exerted proliferative effects on PC-3 and DU-145 prostate cancer cells.…”
Section: Introductionmentioning
confidence: 99%